Measuring Middle School Achievement Trajectories for College Readiness. Issue 7 (November 2022) - Johnson, Angela; Kuhfeld, Megan; King, Gregory
This study identifies students' academic trajectories in the middle grades relative to a set of college readiness benchmarks. We apply math and reading college readiness benchmarks to rich longitudinal data for more than 360, 000 students across the nation. Student-level and school-level demographic characteristics significantly predict academic trajectories. Compared to White and Asian students, higher proportions of Black and Hispanic student are always off-track throughout middle school. Among students who started 6th grade on track, being male, Black, Hispanic, and attending schools with a higher percentage of low-income students are positively associated with falling off track.